MRI of Rheumatic Spine A Case-Based Atlas - D'Aprile, Paola (Springer International Publishing : Imprint: Springer, 2014)
This richly illustrated and comprehensive case-based atlas documents the MR findings observed in spondyloarthritis and offers guidance on selection of the appropriate imaging protocol, which is critical in detecting the potentially very subtle changes. The presented MR study protocols include T2-weighted sequences with fat saturation and contrast-enhanced T1-weighted sequences with fat saturation, these being sequences which permit better visualization of inflammatory changes of both anterior and posterior elements of the spine. Cases of spondylitis, discitis, osteoarthritis, and sacroiliitis are described, and concise information is provided on the clinical history of the rheumatic diseases. The inclusion of a large number of high-resolution images ensures that the atlas will serve as a guide to differentiation between potentially confounding diseases and an aid to early diagnosis, which has become essential with the advent of new treatments in the field of spondyloarthritis (TNF inhibitors). In addition to radiologists, neuroradiologists, rheumatologists, orthopedists, and physiatrists will greatly benefit from the contents of this volume and its thorough presentation of the rheumatic diseases.